Ultra-high energy storage performance with mitigated polarization saturation in lead-free relaxors. Issue 14 (21st March 2019) - Yang, Letao; Kong, Xi; Cheng, Zhenxiang; Zhang, Shujun
Abstract : A strategy of mitigating polarization saturation is applied to enhance the energy storage properties of Sn-modified NBT–ST relaxor ceramics. Abstract : Relaxor ferroelectric ceramics have attracted much attention for storing the electricity generated from clean and renewable energy sources due to their high permittivity and near-zero remnant polarization. The polarization of many relaxor based ceramics tends to saturate at high electric fields, however, which limits their energy storage performance. In this study, a lead-free Sn-modified (Na0.5 Bi0.5 )TiO3 –SrTiO3 system is investigated, where mitigated polarization saturation is observed with the addition of Sn 4+, as a result of the different electronic configurations between d 10 Sn 4+ and d 0 Ti 4+ . As expected, high energy density of 3.4 J cm −3 and energy efficiency of 90% are simultaneously achieved in (Na0.25 Bi0.25 Sr0.5 )(Ti0.8 Sn0.2 )O3 ceramic. In addition, the ceramic exhibits good thermal stability, with the energy storage property variations below 5% over the temperature range of −20 °C to 150 °C, and satisfactory cycling stability with a variation of less than 8% over 10 5 cycles. All these merits demonstrate that the (Na0.25 Bi0.25 Sr0.5 )(Ti0.8 Sn0.2 )O3 ceramic has great potential for high power energy storage applications.